The greens in British politics - Dennison , James (Palgrave Macmillan, 2020)
Contents: Acknowledgements -- 1. The Rise of the Greens in British Politics -- 2. Usual Low in an Improving Context -- 3. 'Green Spike': European Elections to Independence Referendum -- 4. 'Green Surge': Becoming England's Third Largest Party -- 5. Car Crashes, Campaigning and Partial Decline -- 6. Who Voted Green and Why? -- 7. Explaining Constituency-Level Green Success -- 8. Conclusion: Protest, Anti-Austerity and the Divided Left -- Appendices -- Bibliography.